EFFECT OF KISPEPTIN-10 AS AN ALTERNATIVE TO ECG IN ESTRUS SYNCHRONIZATION PROTOCOL ON IMPROVING THE REPRODUCTIVE PERFORMANCE OF KARADI EWES - Abdulkareem, T. A.; Muhammad, S. J.; Yousif, A. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to examine the effect of Kisspeptin-10 as an alternative to equine chorionic gonadotropin (eCG) in estrus- synchronization protocol for improving the reproductive performance of Karadi ewes. Forty adult ewes of 3-7 years old and 65–70 kg live body weight were equally divided into four equal groups. Animals were inserted with a progestagen (60 mg MAP)-impregnated sponges for 13 days as estrus synchronization protocol. Following withdrawal of sponges, first group was served as control (C) and intramuscularly injected with normal saline only. The second group was intramuscularly injected with 250 IU of eCG (eCG), while those of third and fourth groups were intravenously injected with 4 and 8 µg /kg body weight of Kisspeptin-10, referred as Kisspeptin1 and Kisspeptin2 groups respectively. Serum progesterone and LH concentrations did not significantly differ among groups before estrus synchronization protocol and eCG or Kisspeptin treatments. The two Kisspeptin-injected groups attained better (P≤0.01) overall mean estrus (100%), fertility (90%), conception (90 and 100%, respectively), lambing (90%), and twinning (10%) rates with lesser barrenness (10%) as compared with the other groups. Moreover, eCG and Kisspeptin groups exhibited greater (P≤ 0.01) percentage of increasing fecundity (233%) and extra lambs born (0.7) than the control group. In conclusion, treatment of Karadi ewes either with Kisspeptin-10 or eCG hormones enhanced the overall reproductive performance, but did not affect serum progesterone and LH concentrations.